Rekrutierungspotenzial für das Lehramt gewerblich-technischer Fachrichtungen aus dem Beruflichen Gymnasium mit Schwerpunkt Technik? - Graefe, Grit; Temmen, Katrin (Bildung und Beruf, Zeitschrift des Bundesverbandes der Lehrkräfte für Berufsbildung e.V.)

Development of a Strategic Controlling Concept - Fiedler, Moritz

Maturity-based Development of Strategic Thrusts for Socio-technical Risks - Menzefricke, Jörn Steffen; Wiederkehr, Ingrid; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Cost of Debt for Private Firms Revisited: Voluntary Audits as a Reflection of Risk - Ichev, Riste; Koren, Jernej; Kosi, Urska; Sitar Sustar, Katarina; Valentincic, Aljosa
This study examines the relation between voluntary audit and the cost of debt in private firms. We use a sample of 4,058 small private firms operating in the period 2006‐2017 that are not subject to mandatory audits. Firms decide for a voluntary audit of financial statements either because the economic setting in which they operate effectively forces them to do so (e.g., ownership complexity, export‐oriented supply chain, subsidiary status) or because firm fundamentals and/or financial reporting practices limit their access to financial debt, both reflected in earnings quality. We use these factors to model the decision for voluntary audit. In the outcome analyses, we find robust evidence that voluntary audits are associated with higher, rather than lower, interest rate by up to 3.0 percentage points. This effect is present regardless of the perceived audit quality (Big‐4 vs. non‐Big‐4), but is stronger for non‐Big‐4 audits where auditees have a stronger position relative to auditors. Audited firms’ earnings are less informative about future operating performance relative to unaudited counterparts. We conclude that voluntary audits facilitate access to financial debt for firms with higher risk that may otherwise have no access to this form of financing. The price paid is reflected in higher interest rates charged to firms with voluntary audits – firms with higher information and/or fundamental risk.
Keywords: private firms; voluntary audit; cost of debt; self‐selection bias; risk

Himmlischer Warenschatz wohltätiger Erkenntnisse: Gattung und Geschlecht in der Musik - Grotjahn, Rebecca (Gattung und Geschlecht. Konventionen und Transformationen eines Paradigmas)

Zwischen Selbstinszenierung und Werkinterpretation: Solistinnen und Solisten - Grotjahn, Rebecca (Institutionen und Medien)

Musikedition – auch ohne Noten - Iffland, Joachim; Grotjahn, Rebecca (Edieren: Geisteswissenschaften im digitalen Wandel | Éditer : les sciences humaines en mutation)

Singen – Körper – Medien - Grotjahn, Rebecca (Stimmen – Körper – Medien. Gesang im 20. und 21. Jahrhundert)

Angstkonstruktionen zwischen „sinnvoller Vorsicht und sinnloser Panik“ - Georgi, Christopher (Angstkonstruktionen)

Biografie und Werk: Henzes „Bassariden“ - Tumat, Antje (Musik und Homosexualitäten. Tagungsbericht Musikwissenschaftliche Homosexualitätenforschung, Bremen 2017 und 2018)

Digitally Assessing Text Comprehension in Grades 3-4: Test Development and Validation - Seifert, Susanne; Paleczek, Lisa (Electronic Journal of e-Learning)
A prerequisite for child reading support at school is adequate assessment. Embedding (repeated) assessment into daily teaching routine is often challenging for teachers in terms of time and organization. The use of digital tools can help teachers in the assessment process (in preparation, evaluation, documentation, etc.). A digital assessment tool (Graz Reading Comprehension test: GraLeV), focusing on assessing reading comprehension skills in Grades 3 and 4 is currently being developed in Austria. This reading assessment covers reading comprehension at the word, sentence, and text level. Text level is assessed via two subtests (Subtest I: presentation of nonsense-stories and corresponding questions, and Subtest II: maze selection). The other levels consist of one subtest each. This paper focusses on the subtests at text level. More specifically, the paper reports the results of two studies. Study 1 describes the development phases and the first piloting of these two subtests (data collection: 10/2019-12/2019). Testing 273 students with preliminary versions of the subtests (Subtest I: 30 items, Subtest II: 60 items) produced information on (a) item difficulty, (b) item discriminatory power, and (c) time limits for future speed testing. Items not meeting the required quality criteria were excluded. The final version of Subtest I consists of 16 questions referring to eight different, short, nonsense-texts. Its testing time (without instructions) is three minutes. The final version of the Subtest II consists of 2 texts each with 15 maze selections (30 items) and testing time is 100 seconds. The internal consistency is found to be good for Subtest I (α=.87) and Subtest II (α=.78 to .80). Study 2 reports on testing for validity and retest-reliability (data collection: 09/2020-11/2020). Student scores in another reading comprehension test, together with teacher assessments of reading comprehension, were used to assess congruent validity. Divergent validity was assessed using teacher assessments of mathematical and socio-emotional skills. As expected, the correlations with the congruent measures were higher than those with the divergent measures. A subsample was tested twice with the GraLeV. Retest-reliability was acceptable for Subtest II. However, the scores obtained at time 2 were higher compared to those at time 1 in both subtests. This is probably the result of increased student familiarity with the digital device and the digital test environment at time 2. The results are discussed in the light of teachers’ needs for standardized digital assessments in order to facilitate the tailoring of student reading support.
Keywords: Computer Science Applications; Education

Is Reading Comprehension Taken for Granted? An Analysis of Austrian Textbooks in Fourth and Sixth Grade - Seifert, Susanne (Technology, Knowledge and Learning)
Abstract The range of teaching materials now available is becoming increasingly diverse. Despite this, however, the use and influence of textbooks in teaching still remains very high. When instructing reading comprehension, teachers often use textbooks as the basis for teaching in language lessons. Establishing a good match between textbooks and the skills to be acquired is therefore essential. In this paper, I investigate whether textbooks used in Austrian schools can adequately support the teaching of reading comprehension skills. Since reading comprehension is the basis for acquiring knowledge in all subjects, science textbooks are examined in addition to (German) language lesson textbooks. Thus, the content pages of four language textbooks and four science textbooks for fourth and sixth grade were analysed in terms of five different categories, i.e. general structural setup, learning goals, text types, text structures, and activities. The results reveal clear variations with respect to learning goals in language textbooks. For example, the extent to which reading comprehension is addressed ranges from 13.64 to 69.70%, depending on the book used. Although not addressed as a learning goal in the science textbooks, reading comprehension is often presupposed, especially in sixth grade. While the instruction of reading comprehension ought to entail coverage of reading strategies, this is often neglected, or only dealt with indirectly. Given the diversity of textbooks analysed, it seems all the more important to stress that teachers should: 1) clarify the goals and teaching strategies of a book before using it, 2) become aware of strategies that support the development of students' reading comprehension, and 3) use textbooks as a complementary (and not sole) tool to support reading comprehension in all subjects.
Keywords: Computer Science Applications; Human-Computer Interaction; Education; Mathematics (miscellaneous)

The presence of students identified as having special needs as a moderating effect on their classmates’ reading comprehension scores in relation to other major class composition effects - Krammer, Mathias; Seifert, Susanne; Gasteiger-Klicpera, Barbara (Educational Studies)
Keywords: Education

Comparing digital to print assessment of receptive vocabulary with GraWo‐KiGa in Austrian kindergarten - Paleczek, Lisa; Seifert, Susanne; Schöfl, Martin (British Journal of Educational Technology)
Keywords: Education

Teaching and learning in a multilingual Europe: findings from a cross-European study - Dockrell, J. E.; Papadopoulos, T. C.; Mifsud, C. L.; Bourke, L.; Vilageliu, O.; Bešić, E.; Seifert, Susanne; Gasteiger-Klicpera, B.; Ralli, A.; Dimakos, I.; Karpava, S.; Martins, M.; et al. (European Journal of Psychology of Education)
Abstract School classrooms within the EU are multilingual learning environments. The diversity of pupils in classrooms raises significant challenges for teachers, but to date, there are no data from large-scale surveys that compare views within and across European countries. A bespoke questionnaire was designed to examine views of current classroom learning environments with respect to the multilingualism. The questionnaire was piloted and subsequently completed by 2792 teachers across different European countries. Eleven countries provided sufficient data for analyses. Results from structural equation modelling showed that teachers’ attitudes could be reliably measured across Europe with the use of carefully devised questionnaire, whose loading and factor structure remained invariant across countries. Teachers’ views about multilingualism were most challenged by the numbers of children in their classes, not the percentage of multilingual pupils in the class. Countries differed in how they perceived multilingualism, with their differences leading to distinctive country clusters. Gender and education level (elementary vs. secondary) differences were also observed irrespective of country. These findings enhance our understanding of the role that the characteristics of teachers and their classrooms play in a multilingual setting across diverse European settings. The practical relevance of the results and new opportunities for teacher training are discussed.
Keywords: Developmental and Educational Psychology; Education

Die Bedeutung affektiver Merkmale beim Mathematiklernen - Rach, Stefanie; Liebendörfer, Michael (Beiträge zum Mathematikunterricht 2021 vom GDM-Monat 2021 der Gesellschaft für Didaktik der Mathematik (GDM) (1.-25. März 2021))

Increasing the effect of a remedial mathematics course by switching to an online format during the COVID-19 crisis: evidence from a German university - Büchele, Stefan; Liebendörfer, Michael; Lankeit, Elisa (Teaching Mathematics and its Applications: An International Journal of the IMA)
Abstract Due to the COVID-19 crisis, many courses have been offered digitally. Using data from n = 1,173 business students participating in a preparatory mathematics course at a German university that covered the same content as in 2018, 2019 and 2020, we examine how students’ participation and the effect of the preparatory course changed. The data show that the participation rate has fallen slightly, but students’ participation is rather similar to preceding years. Interestingly, students have participated more intensively. There are clear signs of dishonesty in the self-test (use of a calculator) and significant changes in predictors of performance. In particular, the effect of students’ engagement in the course on their performance substantially increased. Further, we found a gender gap in performance affecting women. Finally, the data show that digital courses can be as effective as on-campus courses.
Keywords: Education; General Mathematics

Gymnasiales Lehramt Mathematik studieren – eine Übersicht zur Studienorganisation in Deutschland - Gildehaus, Lara; Göller, Robin; Liebendörfer, Michael (Mitteilungen der Gesellschaft für Didaktik der Mathematik)
Das gymnasiale Lehramtsstudium der Mathematik ist an deutschen Universitäten unterschiedlich organisiert. Traditionell wurden am Studienbeginn die Fachvorlesungen zur Analysis und Linearen Algebra gemeinsam mit Fachstudierenden gehört. In jüngerer Zeit verbreiten sich alternative Modelle z. B. mit Brückenvorlesungen, die oft spezifisch für das Gymnasiallehramt angeboten werden. Sie können gemeinsame Veranstaltungen mit Fachstudierenden ergänzen oder ersetzen. Dieser Beitrag zeigt auf, welche Modelle wie häufig verbreitet sind, und spricht an, welche hochschuldidaktischen Fragen an der Studiengestaltung hängen.

Mathematisierung als Herausforderung für die politische Bildung - Vajen, Bastian; Gildehaus, Lara; Liebendörfer, Michael; Wolf, Christoph (Schriftenreihe der DVPB. Standortbestimmung Politische Bildung: Gesellschaftspolitische Herausforderungen, Zivilgesellschaft und das vermeintliche Neutralitätsgebot)

Prüfungsformate als Ansatzpunkt gendersensibler universitärer Lehre im Fach Mathematik - Göller, Robin; Gildehaus, Lara; Liebendörfer, Michael; Steuding, Jörn (Mathematik und Gender: Berichte und Beiträge des Arbeitskreise Frauen und Mathematik)

Genese und Funktionen von Lerngruppen in der Studieneingangsphase - Haak, Inka; Gildehaus, Lara; Liebendörfer, Michael (Naturwissenschaftlicher Unterricht und Lehrerbildung im Umbruch?)

University students’ fully digital study of mathematics: an identification of student-groups via their resources usage and a characterization by personal and affective characteristics - Kempen, Leander; Liebendörfer, Michael (Teaching Mathematics and its Applications: An International Journal of the IMA)
Abstract We investigated university students’ study of mathematics in the digital setting context of the COVID-19 pandemic. We gathered data from a survey of 89 students enrolled in a ‘Linear Algebra 1’ course including affective variables, learning strategies, social relatedness and resources considered useful. The results indicate students’ high effort and self-regulation and a high variation in affective characteristics and social relatedness. All the traditional aspects of mathematics teaching (lecture, tutorials and lecture notes) were rated as particularly useful. In addition, the videos from external resources were rated as equally useful as the teaching team’s videos. In contrast, traditional literature such as textbooks was rarely considered useful. The most useful resource rated was communication with peers, underlining the important role of social learning despite fully digital learning environments. Finally, a cluster analysis based on students’ rated usefulness of the resources led to three different user-types. Whereas the ‘digitals’ find the external digital resources very useful (videos, webpages, etc.), the ‘traditionalists’ rate the digitalized traditional resources best (lecture, tutorials, etc.). All resources receive uniformly good ratings from a third group (‘all resource users’). We reflect on our findings in light of the pandemic and describe directions for future research.
Keywords: Education; General Mathematics

The Mathematical Beliefs and Interest Development of Pre-Service Primary Teachers - Liebendörfer, Michael; Hochmuth, Reinhard; Rode, Jana; Schukajlow, Stanislaw (Interim Proceedings of the 44th Conference of the International Group for the Psychology of Mathematics Education)

Was bewirkt die Pflichtabgabe von Übungsaufgaben in der Hochschulmathematik? – Ein empirischer Vergleich - Krapf, Regula; Liebendörfer, Michael (mathematica didactica)
Keywords: Extrinsische Motivation

Artificial Intelligence in the Age of Technoscience - Weber, Jutta (Routledge Social Science Handbook of Artificial Intelligence)

Autoethnografie und Kreatives Schreiben - Vochatzer, Stefanie (Journal der Schreibwissenschaft)

Fortbildung to go: Twitter als Ratgeber für Lehrkräfte - Vochatzer, Stefanie; Schröder, Sarah; Fischer, Christian
Keywords: Lehren Digitale Medien Bildungsforschung Weiterbildung Lehrkraft Social Media Förderung

Caroline Rudolphis „Gemälde weiblicher Erziehung“. Einblicke in die Mädchenerziehung der Spätaufklärung - Vochatzer, Stefanie (POSITIONEN)

Festigkeitssteigerung von Aluminiumblechformteilen der 5000-Serie durch Erweiterung der Formgebungsgrenzen stark kaltverfestigter Ausgangswerkstoffe - Camberg, Alan Adam
Leichtmetalle mit einem breiten Eigenschaftsspektrum gewährleisten die Realisierung ressourcenschonender Produkte und ermöglichen die Intensivierung sortenreiner Kreislaufwirtschaften. Die vorliegende Arbeit untersucht einen wärmeunterstützten Ansatz zur Erhöhung der Formgebungsgrenzen stark kaltverfestigter AlMg4,5 Blechwerkstoffe bei gleichzeitiger Beschränkung des Festigkeitsverlustes durch Erholungseffekte. Experimentelle Untersuchungen stellen eine wissenschaftlich fundierte Erkenntnisbasis über die werkstofftechnischen Wirkzusammenhänge des untersuchten Prozesses dar. Gepaart mit an realen Bauteilgeometrien validierten numerischen Simulationsmodellen legt diese Arbeit einen methodischen Grundstein für die industrielle Umsetzung des hier untersuchten Blechumformprozesses. Die erzielte mittlere Dehngrenze des exemplarisch untersuchten Bauteils übersteigt die Dehngrenze eines konventionellen AlMg4,5 Werkstoffes um 190 %. Mit 320 MPa entspricht sie dem Festigkeitsniveau des walzharten Blechhalbzeuges im Lieferzustand, ein Wert, der nach dem aktuellen Stand der Technik auf Bauteilebene ausschließlich mit aushärtbaren AlMgSi Legierungen darstellbar ist.
Keywords: Aluminium; Blechumformung; AlMg; Materialmodellierung; Duktiles Versagen; Halbwarmumformung; Automobil; Leichtbau; Uni-Alloy; 5000-Serie; 5182; GISSMO

Beitrag zur Reduzierung der Fehlerhäufigkeit bei der Online-Lackierung von SMC-Außenhautbauteilen - Huber, Johannes
Der Verbau von Sheet Moulding Compounds im automobilen Außenhautbereich führt in der industriellen Praxis regelmäßig zu abnehmenden Direktläuferquoten in der Technologie Oberfläche, denn neben bekannten Lackierfehlern ergeben sich auch werkstoff-spezifische Oberflächendefekte, welche einen Bauteilwechsel bedingen. Die hier vorliegende Arbeit soll einen aktiven Beitrag zur Reduzierung von Ausschuss und Nacharbeit entlang der Lackierprozesskette leisten. Zu Beginn werden die erfolgskritischen Oberflächendefekte identifiziert und die zugehörigen Fehlerursachen ermittelt, ehe anschließend die Entwicklung der Fehlstellengrößen in Folge der Temperaturbelastung während der Trocknerdurchfahrten untersucht wird. Ferner soll die Auswirkung einer zusätzlich applizierten Oberflächengrundierung auf die Fehlerhäufigkeit sowie die Oberflächengüte im decklackierten Zustand geprüft werden. Als weitere Möglichkeit zur Problemlösung wird eine in den Prozessablauf integrierte Qualitätskontrolle gesehen, weshalb in dieser Arbeit ebenso die Eignung bekannter zerstörungsfreier Prüfmethoden für die präventive Fehlererkennung überprüft und ein zweistufiges Prüfkonzept erarbeitet wird. Das Aufzeigen möglicher Handlungsalternativen sowie die kostentechnische Gegenüberstellung der verschiedenen Anbauvarianten runden die Arbeit ab.
Keywords: Sheet Moulding Compounds; SMC; Online-Lackierung

Konzeptionierung und Auslegung eines Vorderachsträgers in hybrider Leichtbauweise im C-Segment - Pöhler, Simon
Im Rahmen dieser Arbeit wurde ein neuartiger Achsträger in hybrider Bauweise entwickelt und untersucht. Dieser besteht aus einer metallischen Oberschalenstruktur und einer mit Rippen ausgeformten glasfaserverstärkten thermoplastischen Unterschale (GMT), welche zur Einstellung der optimalen Steifigkeit dient. Die Rippen und Unterschale werden hierzu in einem Fließpressverfahren entweder gemeinsam als ein Bauteil oder als separate Einzelteile hergestellt. Durch den lokalen Einsatz von Faserverbundwerkstoffen in der Unterschale und der Rippenstruktur wird ein signifikanter Gewichtsvorteil gegenüber einer Referenzstruktur aus Stahl erzielt. Durch die Verwendung des GMT-Unterbodenschutzes konnten zudem die akustischen Eigenschaften des Fahrwerks hinsichtlich der Dämpfung positiv beeinflusst werden. Die hohen Anforderungen bzgl. Steifigkeit, Festigkeit und Beständigkeit der sicherheitsrelevanten Fahrwerkskomponente konnten unter Einhaltung des Bauraums erfüllt werden. Gleichzeitig konnte das Gesamtgewicht der Komponente im Vergleich zur klassischen Referenzstruktur um 30 % reduziert werden.
Keywords: hybrider Achsträger; Leichtbau; Hybridsysteme

Kooperativ Forschen(d) lernen im inklusiven Sachunterricht der Primarstufe – Ein Theorie-Praxis verzahnter Ansatz zur Vorbereitung von Sachunterrichtsstudierenden auf das Praxissemester - Kirsch, Alexander; Blumberg, Eva; Hellmich, Frank; Hoya, Fabian Karl (Theorie und Praxis in der Lehrerbildung. Verhältnisbestimmungen aus der Perspektive von Fachdidaktiken)

Effects of teacher feedback on children’s self-concepts and motivation in science lessons. 19th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2021. “Education and Citizenship: Learning and Instruction and the Shaping of Futures” - Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

The role of teacher feedback for children’s self-concepts and motivation in primary school science lessons. Single Paper. ECER 2021 (European Conference on Educational Research). “Education and Society: expectations, prescriptions, reconciliations” - Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Ansatz zur Beschreibung von unregelmäßig gefügten Kunststofffilamenten aus Thermoplasten in Wirrmattenstrukturen unter mechanischer Belastung zur Substitution von Schaumstoffen in Polstern und Matratzen - Westhues, Tobias Thomas

Beitrag zur verfahrenstechnischen Entwicklung der Direktcompoundierung im Spritzgießprozess mit sequentiell arbeitenden Kolbenspritzeinheiten - Wittke, Marius

Untersuchung und Prävention der Alterung von Silikon-Gießwerkzeugen beim Polyurethan-Vakuumgießen - Wortmann, Martin

Beiträge zur verfahrenstechnischen Entwicklung der Spritzgießdirektcompoundierung (SGDC) - Jilg, Jannik Richard

Nicht-isotherme Druck-Durchsatzberechnung von Kautschukextrudern - Stüker, Daniel

Global weak solutions in a three-dimensional Keller-Segel-Navier-Stokes system with gradient-dependent flux limitation. - Winkler, Michael (Nonlinear Analysis: Real World Applications)

Suppressing blow-up by gradient-dependent flux limitation in a planar Keller-Segel-Navier-Stokes system. - Winkler, Michael (Zeitschrift für Angewandte Mathematik und Physik)

Can rotational fluxes impede the tendency toward spatial homogeneity in nutrient taxis (-Stokes) systems? - Winkler, Michael (International Mathematics Research Notices)

Boundedness in a three-dimensional Keller-Segel-Stokes system with subcritical sensitivity. - Winkler, Michael (Applied Mathematics Letters)

Does spatial homogeneity ultimately prevail in nutrient taxis systems? A paradigm for structure support by rapid diffusion decay in an autonomous parabolic flow. - Winkler, Michael (Transactions of the American Mathematical Society)

Quo Vadis Conferences in the Business and Information Systems Engineering (BISE) Community After Covid - Leimeister, Jan Marco; Stieglitz, Stefan; Matzner, Martin; Kundisch, Dennis; Flath, Christoph; Röglinger, Maximilian

Influence of pin geometry on the joint strength of CFRT-metal hybrid parts with metallic pins - Popp, Julian; Kleffel, Tobias; Drummer, Dietmar (Joining Plastics)

Energy Efficiency Technologies in Germany - Meschede, Henning

Energie einsparen in Industrie und Gewerbe - Schlosser, Florian; Hechelmann, Ron-Hendrik; Meschede, Henning; Schlüter, Alexander (Das Energiesystem der Zukunft in Smart Cities und Smart Rural Areas)

Mit Energieeffizienz Grundlagen legen - Hechelmann, Ron-Hendrik; Schlosser, Florian; Meschede, Henning; Schlüter, Alexander (Das Energiesystem der Zukunft in Smart Cities und Smart Rural Areas)

Wer grüne Energie will, muss auch koppeln und speichern - Meschede, Henning; Khripko, Diana; Schlüter, Alexander (Das Energiesystem der Zukunft in Smart Cities und Smart Rural Areas)

Energienachfrage flexibler gestalten - Khripko, Diana; Meschede, Henning; Meschede, Eva (Das Energiesystem der Zukunft in Smart Cities und Smart Rural Areas)

Review of infrared spectroscopy techniques for the determination of internal structure in thin SiO2 films - de los Arcos de Pedro, Maria Teresa; Müller, Hendrik; Wang, Fuzeng; Damerla, Varun Raj; Hoppe, Christian; Weinberger, Christian; Tiemann, Michael; Grundmeier, Guido (Vibrational Spectroscopy)

Design of a TiAlON multilayer coating: Oxidation stability and deformation behavior - Bobzin, K.; Kalscheuer, C.; Grundmeier, G.; de los Arcos de Pedro, Maria Teresa; Schwiderek, S.; Carlet, M. (Surface and Coatings Technology)

Produktspezifische Optimierung der Nachhaltigkeit im Ersatzteilmanagement. Ganzheitliche Vorgehensweise zur Bewertung der Nachhaltigkeit additiv gefertigter Komponenten für den Aftermarket - Gräßler, Iris; Hillebrand, Stefan; Thiele, Henrik (Digitalisierung im Kontext von Nachhaltigkeit und Klimawandel)

Moderne Heldin im antiken Gewand? Anne Webers „Annette, ein Heldinnenepos“ - Süwolto, Leonie

In situ backside Raman spectroscopy of zinc oxide nanorods in an atmospheric‐pressure dielectric barrier discharge plasma - Knust, Steffen; Ruhm, Lukas; Kuhlmann, Andreas; Meinderink, Dennis; Bürger, Julius; Lindner, Jörg K. N.; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Journal of Raman Spectroscopy)

Kollusion durch Plattformen - der Einfluss von Tank-Apps auf den Preiswettbewerb von Tankstellen in Deutschland - Heinze, Erik

Big Data in Digital Markets - Challenges for Competition Policy to Protect Consumer Welfare - Rayhan, Shahi

Network Development of Low-Cost Carriers at German Airports - Joshan, Saeid

Optoelectronic sampling of ultrafast electric transients with single quantum dots - Widhalm, Alex; Krehs, Sebastian; Siebert, Dustin; Sharma, Nand Lal; Langer, Timo; Jonas, Björn; Reuter, Dirk; Thiede, Andreas; Förstner, Jens; Zrenner, Artur (Applied Physics Letters)
In our work, we have engineered low capacitance single quantum dot photodiodes as sensor devices for the optoelectronic sampling of ultrafast electric signals. By the Stark effect, a time-dependent electric signal is converted into a time-dependent shift of the transition energy. This shift is measured accurately by resonant ps laser spectroscopy with photocurrent detection. In our experiments, we sample the laser synchronous output pulse of an ultrafast CMOS circuit with high resolution. With our quantum dot sensor device, we were able to sample transients below 20 ps with a voltage resolution in the mV-range.
Keywords: tet_topic_qd

Hybridprofile für Trag- und Crashstrukturen - Drossel, Welf-G; Bobbert, Mathias; Böhme, Marcus; Dammann, Christian; Dittes, Axel; Gießmann, Mina; Hühne, Christian; Ihlemann, Jörn; Kießling, Robert; Lampke, Thomas; Lenz, Peter; Mahnken, Rolf; et al. (Intrinsische Hybridverbunde für Leichtbautragstrukturen)

Constitutive modeling of viscoplasticity including phase transformations for graded thermo‐mechanical processing - Westermann, Hendrik; Reitz, Alexander; Mahnken, Rolf; Grydin, Olexandr; Schaper, Mirko (PAMM)

Damage simulation of thermo‐chemo‐elasto‐plastic fibre reinforced composites using mean‐field homogenization methods - Lenz, Peter; Mahnken, Rolf (PAMM)

An uncertainty model for the curing process of transversely fiber reinforced plastics - Penner, Eduard; Caylak, Ismail; Mahnken, Rolf (PAMM)

Constitutive modeling of dynamic recrystallization coupled to viscoplasticity - Westermann, Hendrik; Mahnken, Rolf (PAMM)

A deep learning driven uncertain full‐field homogenization method - Henkes, Alexander; Caylak, Ismail; Mahnken, Rolf (PAMM)

A non-equilibrium thermodynamic framework for viscoplasticity incorporating dynamic recrystallization at large strains - Mahnken, Rolf; Westermann, Hendrik (International Journal of Plasticity)

Fuzzy and stochastic approach applied to rubber like materials - Penner, Eduard; Caylak, Ismail; Mahnken, Rolf; Dridger, Alex (Safety and Reliability)

On the Thermodynamics of Dynamic Recrystallization for Viscoplasticity at Large Strains - Westermann, Hendrik; Mahnken, Rolf (14th WCCM-ECCOMAS Congress)

Vom rollfähigen zum programmierbaren Fahrzeug. - Scheibe, Volker; Stein, Gerd; Tenberge, Claudia; Bohrmann, Mareike (Die technische Perspektive konkret. Begleitband 5 zum Perspektivrahmen Sachunterricht.)

Anregungen für die Unterrichtspraxis - empfehlenswerte Literatur. - Tenberge, Claudia (Die technische Perspektive konkret. Begleitband 5 zum Perspektivrahmen Sachunterricht.)

"Wie lang ist der Dinosaurier?" Entwicklung eines Messrads zum Messen gekrümmter Linien. - Austermann, Ulrike; Gais, Berenike; Tenberge, Claudia (Die technische Perspektive konkret. Begleitband 5 zum Perspektivrahmen Sachunterricht.)

Plattformgestaltungen auf digitalen Märkten - eine Analyse der Wohlfahrtseffekte - Ajredini, Zurkani

320 GHz Analog-to-Digital Converter Exploiting Kerr Soliton Combs and Photonic-Electronic Spectral Stitching - Fang, Dengyang; Drayß, Daniel; Lihachev, Grigory; Marin-Palomo, Pablo; Peng, Hui; Füllner, Christoph; Kuzmin, A; Liu, J; Wang, Ruoyu; Snigirev, Viacheslav; Lukashchuk, Anton; Zang, M; et al. (2021 European Conference on Optical Communication (ECOC))
We demonstrate a photonic-electronic analog-to-digital converter (ADC) offering a record-high acquisition bandwidth of 320 GHz. The system combines a high-speed electro-optic modulator with a Kerr comb for spectrally sliced coherent detection and is used for digitizing ultra-broadband data signals.

Technological and Inclusive Education - Considering Students’ Needs Towards Technological Learning in Primary Schools - Schröer, Franz; Tenberge, Claudia (TECHNE SERIES - Forskning i slöjdpedagogik och slöjdvetenskap)
Research on technological educationininterdisciplinary scienceand socialstudies (Sachunterricht) in German primary schools emphasizes that childrenare generally interested in technology. While several STEAM initiatives point towards a growing recognition of technological literacy, the consideration of technology education ininterdisciplinaryscience and social studies is quite underrepresented in practice as well as in research and teacher training.Takinginto accountthe UN-CRPDclaims foran inclusive educational system andthus alsothe right to equally participate in a free society,participation in society through participation in technological development is a fundamental common goal of technological and inclusive education and part of widely recognized technological literacy.It is therefore not well understood how teaching and learning arrangementscan consider and satisfythe needs of all different students. The research project the present paper is part of tries to unveil the appearance of student’s basic needs in relation to technological educationfor all children. Thisinitial quantitative part of a grounded theory study examined the subjective significance of basic psychological needs in interdisciplinary science studies in primary educationto allow for a well-reasoned sample choice for subsequent interviews. Quantitative results point towards some revisions regarding the instrument used and several implications on the diversity of students ́needs in science and social studies. Future research is needed with larger samples for factor-analysis.
Keywords: Inclusion; basic needs; Technology Education; Primary Education; autonomy; competence; social relatedness

Inklusionskompetenz von Lehramtsstudierenden im Vergleich dreier europäischer Bildungssysteme – Ergebnisse aus dem Forschungsprojekt. Vortrag. Abschlussveranstaltung der Förderlinie "Qualifizierung der pädagogischen Fachkräfte für inklusive Bildung" des Bundesministeriums für Bildung und Forschung (BMBF) - Albers, Timm; Filipiak, Agnes; Franzen, Katja; Hellmich, Frank

Inklusionskompetenz von Lehramtsstudierenden im Vergleich dreier europäischer Bildungssysteme –Schlussfolgerungen und Implikationen. Vortrag. Abschlussveranstaltung der Förderlinie "Qualifizierung der pädagogischen Fachkräfte für inklusive Bildung" des Bundesministeriums für Bildung und Forschung (BMBF) - Albers, Timm; Filipiak, Agnes; Franzen, Katja; Hellmich, Frank

Determinants for teachers’ intentions to manage heterogeneity in (non-)inclusive primary education. 19th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2021. “Education and Citizenship: Learning and Instruction and the Shaping of Futures” - Görel, Gamze; Löper, Marwin Felix; Hellmich, Frank

Primary school students’ contact experiences and their attitudes towards peers with disabilities. 19th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2021. “Education and Citizenship: Learning and Instruction and the Shaping of Futures” - Löper, Marwin Felix; Schwab, Susanne; Hellmich, Frank

Individual prerequisites for children’s attitudes towards peers with social-emotional disabilities. 19th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2021. “Education and Citizenship: Learning and Instruction and the Shaping of Futures” - Löper, Marwin Felix; Hellmich, Frank

The prediction of primary school teachers’ self-efficacy expectations in inclusive education. Single Paper. ECER 2021 (European Conference on Educational Research). “Education and Society: expectations, prescriptions, reconciliations” - Franzen, Katja; Moschner, Barbara; Hellmich, Frank

Primary school principals’ views on designing inclusive schools. 19th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2021. “Education and Citizenship: Learning and Instruction and the Shaping of Futures” - Görel, Gamze; Hellmich, Frank

Die Bedeutung von Erfahrungen für die Einstellungen von Grundschulkindern gegenüber Peers mit emotional-sozialen Schwierigkeiten im inklusiven Unterricht. Vortrag auf der Tagung der Arbeitsgruppe empirische sonderpädagogische Forschung - Löper, Marwin Felix; Lehofer, Mike; Schwab, Susanne; Hellmich, Frank

Unterscheiden sich Lehrkräfte an inklusiven und nicht-inklusiven Grundschulen hinsichtlich ihrer Handlungsintentionen bei der Gestaltung adaptiven Unterrichts? Vortrag auf der Tagung der Arbeitsgruppe empirische sonderpädagogische Forschung - Löper, Marwin Felix; Görel, Gamze; Hellmich, Frank

Mentale Rotationsleistungen bei der Betrachtung und Umsetzung von Spielzügen im Basketball: Novizen vs. erfahrene Basketballspieler - Krause, Daniel; Behrens, J.B.; Löhers, L.; Weigelt, Matthias

Singen – Körper – Medien - Grotjahn, Rebecca (Stimmen – Körper – Medien. Gesang im 20. und 21. Jahrhundert)

Multiprofessionelles und inter-institutionelles Netzwerken als Element sozialraumorientierten Handelns - Landhäußer, Sandra (Sozialraumorientierung: Innovation durch Kleinräumigkeit? Die Perspektive der Kinder- und Jugendhilfepraxis)
Das Programm Sozialraumorientierung bietet sich seit etwa dreißig Jahren als zentrale strategische Option präventiver Sozialpolitik an. Mit den Zielen Dezentralisierung der Organisation, Aktivierung der lokalen Gemeinschaft zur Behebung lokaler Problemlagen und (bessere) Partizipation der Anwohner_innen verspricht Sozialraumorientierung ebenso eine administrative wie fachliche Innovation sowie eine fiskalische Entlastung durch höhere Effizienz. Dieses omnipotente Versprechen macht das Programm Sozialraumorientierung gerade für kommunale Steuerungsinstanzen oder Leitungsinstanzen großer Träger von Jugendhilfeleistungen höchst attraktiv. Doch wie schätzen die Akteur_innen im Feld das Programm Sozialraumorientierung ein? Die konkreten Deutungs- und Wissensmuster der unterschiedlichen professionellen Akteur_innen, die auf den Ebenen Bundesland und Kommune die Einführung und Umsetzung des Programms Sozialraumorientierung mitverantworten, stehen im Mittelpunkt des vorliegenden Bandes. Basis sind die Ergebnisse eines aktuellen Forschungsprojektes, die im ersten Teil ausführlich vorgestellt werden und im zweiten Teil von deutschsprachigen Expert:innen aus unterschiedlichen Perspektiven diskutiert werden.
Keywords: Jugendhilfe | Sozialraum | Soziale Arbeit | Kinderschutz | Sozialplanung

Von sozialer Exklusivität und „sozialem Sprengstoff“ – Perspektiven von Lehr- und Leitungskräften auf Differenz und Ungleichheit in der Ausbildung von Erzieher_innen - Kuhn, Melanie; Landhäußer, Sandra (Diskurs Kindheits- und Jugendforschung)
Angehende Erzieher_innen sollen an Fachschulen für Sozialpädagogik für einen professionellen Umgang mit Differenz in ihrer späteren Berufspraxis ausgebildet werden. Diese Professionalisierung an Fachschulen findet aber auch in institutionellen Kontexten statt, die selbst von gesellschaftlichen Differenz- und Ungleichheitsverhältnissen geprägt sind. Gezeigt wird in einer kontrastierenden Analyse zweier Expert_inneninterviews mit einer Lehr- und einer Leitungskraft von Fachschulen, dass die wahrgenommene soziale Positioniertheit der eigenen Schüler_innen präformiert, wie die breiten curricularen Vorgaben zur differenzbezogenen Professionalisierung konkretisiert werden und welche inhaltlichen Schwerpunkte die Schulen setzen.
Keywords: Erzieher_innenausbildung; Fachschule für Sozialpädagogik; Differenz; Ungleichheit; Expert_inneninterviews

Zeit als Widerfahrnis. Ästhetik und Figuration passiv erfahrener Temporalität - Öhlschläger, Claudia; Roselli, Antonio (ZfdPh)

Haus-Komödien: Renaissancen des Lustspielsbei Ludovico Ariosto und William Shakespeare ("I Suppositi", "The Taming of the Shrew") - Steigerwald, Jörn (Gattung und Geschlecht. Konventionen und Transformationen eines Paradigmas.)

Base-Free Catalytic Wittig-/Cross-Coupling Reaction Sequence as Short Synthetic Strategy for the Preparation of Highly Functionalized Arylbenzoxepinones - Werner, Thomas; Grandane, Aiga; Pudnika, Linda; Domraceva, Ilona; Zalubovskis, Raivis (Synthesis)
Abstract The facile synthesis of highly functionalized building blocks with potential biological activity is of great interest to medicinal chemistry. The benzoxepinone core structures commonly exhibit biological activity. Thus, a short and efficient synthetic route towards benzoxepine containing scaffold, which enables late stage modification was developed. Namely, base-free catalytic Wittig reactions enabled the synthesis of bromobenzoxepinones from readily available starting materials. Subsequent, Suzuki–Miyaura and Stille reactions proved to be suitable methods to access a variety of benzoxepinone diaryl derivatives by late stage modification in only three steps. This three-step reaction sequence is suitable for high throughput applications and gives facile access to highly complex molecular structures, which are suitable for further functionalization. The antiproliferative properties of selected arylbenzoxepinones were tested in vitro on monolayer tumor cell line A549. Notably, in this initial screening, these compounds were found to be active in the micromolar range.
Keywords: Organic Chemistry; Catalysis

Organische Chemie - Paradies, Jan; Andexer, Jennifer; Beifuss, Uwe; Beuerle, Florian; Brasholz, Malte; Breinbauer, Rolf; Ernst, Martin; Ganardi, Ruth; Gulder, Tobias A. M.; Hüttel, Wolfgang; Kath‐Schorr, Stephanie; Körber, Karsten; et al. (Nachrichten aus der Chemie)
Keywords: General Chemical Engineering; General Chemistry

Indirect reduction of CO2 and recycling of polymers by manganese-catalyzed transfer hydrogenation of amides, carbamates, urea derivatives, and polyurethanes - Liu, Xin; Werner, Thomas (Chemical Science)
A Mn–PNP complex proved to be a suitable catalyst for the transfer hydrogenation of amides, carbamates, urea derivatives and even polyurethanes.
Keywords: General Chemistry

Poly(methylhydrosiloxane) as a reductant in the catalytic base-free Wittig reaction - Tönjes, Jan; Longwitz, Lars; Werner, Thomas (Green Chemistry)
PMHS proved to be a suitable terminal reductant for P(iii)/P(v) redox cycling with a methyl-substituted phosphetane as catalyst and BuOAc as solvent. The formation of water by silanol condensation was identified as main pathway of siloxane formation.
Keywords: Pollution; Environmental Chemistry

Representations after mentally practiced one finger sequences are effector independent - Dahm, Stephan; Weigelt, Matthias; Rieger, M.

AMPA-15N – Synthesis and application as standard compound in traceable degradation studies of glyphosate - Wirth, Marisa A.; Longwitz, Lars; Kanwischer, Marion; Gros, Peter; Leinweber, Peter; Werner, Thomas (Ecotoxicology and Environmental Safety)
Keywords: Health; Toxicology and Mutagenesis; Public Health; Environmental and Occupational Health; Pollution; General Medicine

Mental body rotation with egocentric and object-based transformations in different postures: sitting vs. standing - Budde, Kirsten; Barela, J.A.; Figueiredo, G.A.; Weigelt, Matthias

Towards the Development of Frustrated Lewis Pair (FLP) Catalyzed Hydrogenations of Tertiary and Secondary Carboxylic Amides - Paradies, Jan; Köring, Laura; Sitte, Nikolai A. (Synthesis)
Abstract The development of the frustrated Lewis pair catalyzed hydrogenation of tertiary and secondary amides is reviewed. Detailed insight into our strategies in order to overcome challenges during the reaction development process is provided. Furthermore, the developed chemistry is extended to the hydrogenation of polyamides and of trifluoroacetamides for the convenient introduction of trifluoroethyl groups into organic molecules.
Keywords: Organic Chemistry; Catalysis

Borane Catalyzed Redox Isomerization of 2‐Amino Chalcones: Hydride Abstraction or Hydride Migration? - Zhou, Rundong; Paradies, Jan (European Journal of Organic Chemistry)
Keywords: Organic Chemistry; Physical and Theoretical Chemistry

Diastereoselective Synthesis of Dihydro-quinolin-4-ones by a Borane-Catalyzed Redox-Neutral endo-1,7-Hydride Shift - Wicker, Garrit; Schoch, Roland; Paradies, Jan (Organic Letters)